2005
DOI: 10.1038/nm1248
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory arthritis requires Foxo3a to prevent Fas ligand–induced neutrophil apoptosis

Abstract: In inflammatory arthridities such as rheumatoid arthritis, cognate lymphocytes have long been considered instigators of autoimmunity, but accumulating evidence indicates that innate immune cells such as neutrophils and mast cells are responsible for a vast majority of acute and ongoing inflammation; however, the molecular mechanisms that govern them remain largely unknown. Here we show that such inflammation requires the forkhead transcription factor Foxo3a: Foxo3a-deficient mice are resistant to two models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
172
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(190 citation statements)
references
References 29 publications
11
172
3
Order By: Relevance
“…18 In line with the prolonged life span of neutrophils in the absence of endogenous IFN-b, decreased expression of Fas on neutrophils derived from tumors ( (Fig. 2a).…”
Section: Decreased Fas Expression On Neutrophils From Tumor Bearing Isupporting
confidence: 62%
“…18 In line with the prolonged life span of neutrophils in the absence of endogenous IFN-b, decreased expression of Fas on neutrophils derived from tumors ( (Fig. 2a).…”
Section: Decreased Fas Expression On Neutrophils From Tumor Bearing Isupporting
confidence: 62%
“…Our work demonstrated that miR-484 regulates Fis1 through targeting the amino acid coding sequence. Noticeably, Foxo3a can inhibit apoptosis 19,44 . In consistence with the anti-apoptotic function of Foxo3a, we identified that Foxo3a can transactivate miR-484 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are also reports showing that it can inhibit apoptosis 19,44 . It stimulates the expression of the anti-apoptotic factors including manganese superoxide dismutase 48 and catalase 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA samples recovered from DNA-Protein immunocomplexes were amplified by PCR using the following primer sets: 38 …”
Section: Chip Assaymentioning
confidence: 99%